1992
DOI: 10.1007/bf00228999
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids and N-acetyl-aspartyl-glutamate as neurotransmitter candidates in the monkey retinogeniculate pathways

Abstract: The identity of the neurotransmitter(s) in the mammalian retinogeniculate pathway is unclear. To investigate the possibility that some amino acids and certain dipeptides, such as N-acetyl-aspartyl-glutamate (NAAG), fulfill this function, changes in their concentration were measured in the optic tract, and the parvocellular and magnocellular segments of the LGNd of six monkeys (Macaca fascicularis), seven days after right optic tractotomy. The LGNd was studied also in two additional macaques, three months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Urine was also collected from groups of four Pcmt1-/-and four Pcmt1ϩ/ϩ mice housed in metabolic cages. NAAG and ␤-NAAG were isolated with a high performance liquid chromatography system (two model 510 pumps with a U6K injector and a model 441 absorbance detector set to 214 nm), according to published procedures (29). Aliquots of brain cytosol (100 l, 0.99 -2.14 mg/ml) and urine (100 l) were injected onto an anion-exchange column (Partisil SAX; particle size, 10 m; 250 ϫ 4.6 mm; Alltech) equilibrated in 60 mM monopotassium phosphate, pH 4.5, and the peptides were eluted isocratically at 1.0 ml/min.…”
Section: Methodsmentioning
confidence: 99%
“…Urine was also collected from groups of four Pcmt1-/-and four Pcmt1ϩ/ϩ mice housed in metabolic cages. NAAG and ␤-NAAG were isolated with a high performance liquid chromatography system (two model 510 pumps with a U6K injector and a model 441 absorbance detector set to 214 nm), according to published procedures (29). Aliquots of brain cytosol (100 l, 0.99 -2.14 mg/ml) and urine (100 l) were injected onto an anion-exchange column (Partisil SAX; particle size, 10 m; 250 ϫ 4.6 mm; Alltech) equilibrated in 60 mM monopotassium phosphate, pH 4.5, and the peptides were eluted isocratically at 1.0 ml/min.…”
Section: Methodsmentioning
confidence: 99%
“…At the retinogeniculate synapse, the connection between retinal ganglion cells (RGCs) in the eye and thalamic relay neurons in the lateral geniculate nucleus (LGN), transmission is mediated via glutamatergic synapses containing both ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) and N-methyl-D-aspartate receptors (NMDARs) (Chen and Regehr 2000;Kemp et al 1982;Molinar-Rode and Pasik 1992;Mooney et al 1993;Salt 1986). Large-scale refinement of the retinogeniculate synapse has been demonstrated in the rodent over a developmental period spanning three postnatal weeks as synaptic strength increases, and the number of RGCs that innervate a given relay neuron is reduced from more than 10 inputs to 1-3 inputs (Chen and Regehr 2000;Hooks and Chen 2006;Jaubert-Miazza et al 2005;Ziburkus and Guido 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In general, NAAG-IR in the rat forebrain does not correlate well with putative glutamatergic systems (Moffett et al, , 1993Moffett and Namboodiri, 1995), one of the major exceptions being the retinal projections. NAAG-IR has been observed in the majority of retinal ganglion cells in every avian and mammalian species studied to date and is found in retinal terminals in all visual target areas (Tieman et al, 1987(Tieman et al, , 1988(Tieman et al, , 1991bMoffett et al, 1990Moffett et al, , 1991aWilliamson et al, 1991;Molinar-Rode and Pasik, 1992;Tieman and Tieman, 1996). Despite its phylogenetically conserved nature, the role of NAAG in the primary visual projections is unclear; electrophysiological investigations with NAAG application have yielded variable results (Jones and Sillito, 1992).…”
Section: Discussionmentioning
confidence: 96%
“…Ultrastructural immunocytochemical studies have demonstrated high levels of glutamate immunoreactivity in synaptic terminals of retinal origin (Montero and Wenthold, 1989;Montero, 1990;Cardozo et al, 1991). A nervous system-specific dipeptide, N-acetylaspartylglutamate (NAAG), also is found in very high concentrations in the visual system of mammals, e.g., 3.86 mol/g weight in the optic tract of monkeys (Molinar-Rode and Pasik, 1992). It is localized in most retinal ganglion cells; in the optic nerves, chiasm, and tracts; and in the neuropil of all retinal target areas (Tieman et al, 1987(Tieman et al, , 1988(Tieman et al, , 1991aAnderson et al, 1987;Moffett et al, 1990).…”
mentioning
confidence: 98%